Possible Evidence for Distortions in The Australian Height Datum in Western Australia - Featherstone, Will; Stewart, Michael (Institution of Surveyors, Australia, 1998)
The Western Australian STATEFIX GPS network, used in conjunction with the EGM96 global geopotential model, indicates the possible presence of distortions in the Australian Height Datum (AHD) over this state. The differences between 63 STATEFIX-EGM96 and AHD heights agree well with the differences between free and fixed-network adjustments of the AHD, published by Roelse et al. (1971). The agreement between these two sources of height information suggests that the most likely source of these differences lies within the AHD due to its constraint to mean sea level at 30 tide gauges around the Australian coast.